Deep Relationship Between the “Haha!” of Humor and the “A-ha!” of Learning: Context-Based Comic Book Development, Teacher and Student Opinions - YÜZBAŞIOĞLU, Mustafa Kemal; KURNAZ, Mehmet Altan (Afyon Kocatepe University, 2023)
The research aimed to determine the opinions of the students and the course teacher with regard to using the comic book prepared in accordance with a context-based scenario as teaching material for the science course. Phenomenology, one of the qualitative research approaches, was used for research purposes. A context-based comic book was used as course material for 12 hours in a class of 18 5th-grade students. Semi-structured interviews were conducted with seven students and a course teacher, following the implementation, using the interview forms developed within the scope of the current research. The data obtained from the interviews were analyzed by content analysis and classified under the themes of “Academic”, “Affective”, “Association with Daily Life” and “Comic Books and Humor”. Pursuant to the results of the research, students, and course teacher declared the comic book as effective course material on the grounds that it makes the subject matter entertaining and understandable, facilitates learning, provides an opportunity for a permanent learning experience, provides an opportunity for individual learning, increases class participation and supports the learning processes of students with literacy and language problems. Based on the results obtained, it has been suggested to use context-based comics in different units and lessons.
Keywords: Bağlam temelli öğrenme; çizgi roman; mizah; fen eğitimi.; Mizah; Alan Eğitimleri; Humor; Bağlam Temelli Öğrenme; Context-based learning; comic books; humor; science education.; Other Fields of Education; Science Education; Context-Based Learning; Fen Eğitimi; Comic Books; Çizgi Roman; 4. Education; 16. Peace & justice; 3. Good health; 5. Gender equality; 10. No inequality